A Hollow Porous Metal‐Organic Framework Enabled Polyethylene Oxide Based Composite Polymer Electrolytes for All‐Solid‐State Lithium Batteries. Issue 3 (27th December 2021) - Hu, Yubing; Feng, Tianshi; Xu, Lei; Zhang, Lifeng; Luo, Langli
Abstract: Composite polymer electrolytes (CPEs) are replacing traditional liquid electrolytes for next‐generation all‐solid‐state batteries (ASSBs) with enhanced safety and uncompromising electrochemical properties. However, short‐circuit due to lithium‐dendrite growth in the CPEs largely hinders its practical applications. Here, we report a thin CPE composed of the hollow ZIF‐8 encapsulating Li‐ionic liquids (ZIF‐8/IL) nano‐fillers and polyethylene oxide (PEO) matrix. It shows an ionic conductivity of 1.41×10 −4  S cm −1 at 25 °C with improved surface roughness, thermal stability, and electrochemical stability. The specific core‐shell structure of fillers benefits from its insulation shell for inhibiting lithium dendrite growth and the inner cavity for storing sufficient Li‐IL with enhanced Li diffusivity. The CPE with 30 % filler (30 H‐Z CPE) content exhibits excellent cycle stability of 770 h in the Li symmetric cell and an outstanding discharge capacity of 182.5 mAh g −1 and capacity retention of 73 % after 100 cycles at 0.1 C and 60 °C in the Li/30 H‐Z CPE/NCM811 asymmetric cell. Abstract : Composite polyelectrolyte for all‐solid‐state batteries : The specific core‐shell structure of the hollow ZIF‐8 encapsulating Li ionic liquid (Li‐IL) nano‐fillers benefits from its insulating shell for inhibiting lithium dendrite growth and the inner cavity for storing sufficient Li‐IL with enhanced Li diffusivity. The thin CPE composed of the novel fillers and polyethylene oxide matrix shows an outstanding electrochemical performance and stability.